CHARACTERISTICS OF HEARING THINGS ON MUSIC PLAYERS AT GPT BAITHANI DENPASAR - Pinatih, Ketut Tadeus Max Nurcahya; Wiranadha, I Made (E-Jurnal Medika Udayana; Vol 11 No 9 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i9.P05, 2022)
Background: Noise Induced Hearing Loss (NIHL) is hearing loss due to exposure to loud enough noise for a long period of time. The deafness characteristic of noise-induced hearing loss is that cochlear sensorineural deafness that cannot be treated. Playing music is one of the important risk factors that can lead to noise-induced hearing loss among musicians. Musicians in the church regularly play music for every worship event at the church. Therefore, researchers want to know the threshold of hearing among musicians at GPT Baithani Denpasar. Methods: This study is a descriptive study using a cross sectional design, by taking primary data from history taking, physical examination and audiometric examination. Samples were taken by means of total sampling. Data analysis was carried out using the SPSS 24 program and the research results were presented in the form of tables and narratives which were then described descriptively to describe the characteristics of the subjects and research variables. Result: This study involved 18 samples, all male (100%). The age range of music players is between 18-40 years, and they have been playing music for more than 5 years. Music players consist of 5 instruments, namely three keyboards (16.7%), six bass players (33.3%), four guitars (22.2%), four drums (22.2%), and one violin (5.5%). The incidence of NIHL found one musician with a duration of practice seven times per week (5.6%), one musician with a six times per week (5.6%), and one musician four times per week (5, 6%). Conclusion: There is a mild degree of hearing loss as many as three music players (16.7%). One music player has interference in the left ear, one music player has interference in the right ear, and one music player has interference in both ears Keyword: Noice Induce Hearing Loss (NIHL), music